2012
DOI: 10.1523/jneurosci.3474-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlation Is Stimulus Modulated by Feedforward Inhibitory Circuitry

Abstract: Correlated variability of neural spiking activity has important consequences for signal processing. How incoming sensory signals shape correlations of population responses remains unclear. Cross-correlations between spiking of different neurons may be particularly consequential in sparsely firing neural populations such as those found in layer 2/3 of sensory cortex. In rat whisker barrel cortex, we found that pairs of excitatory layer 2/3 neurons exhibit similarly low levels of spike count correlation during b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 68 publications
6
101
0
Order By: Relevance
“…We next studied the dynamics of the population in response to short acoustic clicks (duration, 5 ms; interclick interval, 2.5 or 3.5 s). We used a sliding spike count window (T = 50 ms) and computed the averaged instantaneous rate, spike count correlation ρ(t) (2,14,15), and spike count Fano factor (11)(12)(13) by performing the statistics across repeated stimulus presentations and averaged over single units or single-unit pairs (Methods). Similarly, we computed the instantaneous silence density S(t) using 20-ms bins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next studied the dynamics of the population in response to short acoustic clicks (duration, 5 ms; interclick interval, 2.5 or 3.5 s). We used a sliding spike count window (T = 50 ms) and computed the averaged instantaneous rate, spike count correlation ρ(t) (2,14,15), and spike count Fano factor (11)(12)(13) by performing the statistics across repeated stimulus presentations and averaged over single units or single-unit pairs (Methods). Similarly, we computed the instantaneous silence density S(t) using 20-ms bins.…”
Section: Resultsmentioning
confidence: 99%
“…In anesthetized rodents correlations decrease with brain state desynchronization (8,9) or when animals switch from quiet wakefulness to active whisking during waking (10). Moreover, the commonly observed drop of spiking variability following stimulus onset (11)(12)(13) seems to occur jointly with a transient decrease in correlation (2,14,15). These observations suggest that correlations reflect the dynamical state of the circuit more than its hardwired connectivity.…”
mentioning
confidence: 95%
“…Computational modeling has demonstrated that variability shaping can be caused by nonlinearities that alter the distribution of neural activity. Electrodes with positive signal correlations are decorrelated during stimulus representation because they receive a common feedforward input that changes the response distribution (Middleton et al, 2012). However, it is unclear how this change in the shape of variance on the scale of neurons would generalize to aggregate neural populations in ECoG.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the thresholding associated with spike generation, the transfer of correlations from synaptic inputs to spiking output is highly nonlinear (Lampl et al, 1999;Binder and Powers, 2001;Dorn and Ringach, 2003;Shamir and Sompolinsky, 2004;de la Rocha et al, 2007;Shea-Brown et al, 2008;Burak et al, 2009;Tchumatchenko et al, 2010;Middleton et al, 2012). For example, even when total input correlation is constant, total output correlation can vary with changes in input strength, resulting in a positive dependency between the mean spike rate and total correlation in cortical spiking (de la Rocha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%